Polymorphism of major histocompatibility complex extended haplotypes bearing HLA-DR3 in patients with rheumatoid arthritis with gold induced thrombocytopenia or proteinuria. Issue 8 (August 1990) - Singal, D P; Reid, B; Green, D; D'Souza, M; Bensen, W G; Buchanan, W W
Abstract : The distribution of DR3 and of extended haplotypes bearing DR3 was studied in three groups of subjects: 35 patients with rheumatoid arthritis (RA) with gold induced thrombocytopenia or proteinuria, 185 patients with RA without these side effects, and 300 normal healthy controls. The extended haplotypes bearing DR3 were analysed with cDNA probes for DR alpha, DR beta, DQ alpha, and DQ beta genes. The data showed that the prevalence of DR3 was significantly higher in patients who developed gold induced thrombocytopenia or proteinuria than in normal controls or patients with RA without these side effects. Distribution of three extended haplotypes bearing DR3 (B8, DR3; B18, DR3; non-B8, non-B18, DR3) in patients with RA with thrombocytopenia or proteinuria was significantly different from that in normal controls, but not from that in patients with RA without these toxic reactions. Southern blot analysis of DR, DQ genes with cDNA probes showed that the extended haplotype bearing B8, DR3, which carries DQA2.1 and DQB2.1 genes, was present in a significantly higher proportion of patients with RA with gold induced thrombocytopenia or proteinuria (22/24, 92%) than in patients with RA without these side effects (32/45, 71%) or normal subjects (40/61, 66%). The data suggest that the genomic region on chromosome 6 involved in susceptibility to gold induced thrombocytopenia or proteinuria should be extended to the DQA2, DQB2 gene loci.